Hydrolytic conversion of a metal-organic polyhedron into a metal-organic framework - Mallick, Arijit; Garai, Bikash; Diaz, David Diaz; Banerjee, Rahul (Angewandte Chemie-International Edition, 2013)
Keywords: cage compounds; crystal engineering; hydrophobic effect; metal-organic frameworks; Self-assembly

Highly stable covalent organic framework-Au nanoparticles hybrids for enhanced activity for nitrophenol reduction - Pachfule, Pradip; Kandambeth, Sharath; Diaz, David Diaz; Banerjee, Rahul (Chemical Communications, 2014)
{Gold [

Homogeneous photochemical water oxidation by biuret-modified Fe-TAML: evidence of Fe-V(O) intermediate - Panda, Chakadola; Debgupta, Joyashish; Diaz, David Diaz; Singh, Kundan K.; Gupta, Sayam Sen; Dhar, Basab B. (Journal of the American Chemical Society, 2014)
{Water splitting, leading to hydrogen and oxygen in a process that mimics natural photosynthesis, is extremely important for devising a sustainable solar energy conversion system. Development of earth-abundant, transition metal-based catalysts that mimic the oxygen-evolving complex of photosystem II, which is involved in oxidation of water to O-2 during natural photosynthesis, represents a major challenge. Further, understanding the exact mechanism, including elucidation of the role of active metal-oxo intermediates during water oxidation (WO), is critical to the development of more efficient catalysts. Herein, we report Fe-III complexes of biuret-modified tetra-amidomacrocyclic ligands (Fe-TAML; 1a and 1b) that catalyze fast, homogeneous, photochemical WO to give OD with moderate efficiency (maximum TON = 220